Efektivitas Metode Magic Number untuk Penyelesaian Soal-Soal Energi Kinetik Relativistik - Ferdi Yusril Hikam Suharsono; Widari Kusuma; Faizzatul Ummah; Eza Bintang Ramadhan; Bambang Supriadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
Abstract: The purpose of this study was to determine the effectiveness of using the magic number method, the development of the Pythagorean method by Korkmaz to solve the State University Joint Selection Entrance Questions (SBMPTN) chapter on particular relativity theory, sub-chapter relativistic kinetic energy in class XI MIPA 3 SMA State Plus Sukowono. The research method uses the experimental process-data collection techniques in the form of student learning outcomes tests. After presenting the relativistic kinetic energy material using the usual way and the magic number method, students were given five questions with a processing time of 30 minutes. The results obtained that the average value using the standard working method is 70.7 while using the magic number is 78.7. In conclusion, using the magical number method in solving problems of relativistic kinetic energy for students proved to be effective and positively affected student learning outcomes. Keywords: Effectiveness, Physics, Magic Number, Relativity